Turning tables: Redesigning virtual exchange through the learners' experience - Rampazzo, Laura [UNESP]; Moore, Viviane Klen-Alves [UNESP] (Ubiquity Press, 2024)
In our increasingly interconnected world, we need to effectively build relationships and communicate with people from diverse cultures and linguistic backgrounds. The Covid-19 pandemic emphasized the use of digital tools and worldwide collaboration. Tandem Learning (Brammerts, 1996) connects learners from different backgrounds to assist each other in learning their languages and cultures (Telles & Vassallo, 2006). These practices have branched out from face-to-face environments to virtual exchange (VE) projects (O'Dowd, 2018). In this context, this chapter explores language learners' experiences with VE to advance programs' design and continuous development. In 2022, students from a South American institution participated in a tandem-based VE with students from North American universities. Students communicated synchronously in English and Portuguese for an extended period of time and worked in dyads to achieve the language goals they had set for themselves and complete the VE program. Following a mixed-methods approach, this study analyzes 26 learners' perspectives in a post-participation questionnaire and how these may help redesign the practice. The participants' evaluations provide valuable insights for redesigning VE projects, helping practitioners identify successful aspects to be replicated and areas needing improvement. These findings can assist other educators in promoting VEs to enhance language learning and cultural understanding.